Female fertility and infant survivorship increase following lethal intergroup aggression and territorial expansion in wild chimpanzees - Brian M. Wood; David P. Watts; Kevin E. Langergraber; John C. Mitani (Proceedings of the National Academy of Sciences, 2025)
Lethal coalitionary intergroup aggression is a conspicuous aspect of wild chimpanzee behavior. Evidence indicates that such violence can lead to territorial expansion, but whether this results in fitness benefits is unknown. Here, we show that female fertility and infant survivorship increased after males in the Ngogo chimpanzee community killed members of neighboring groups and expanded their territory. These findings demonstrate the fitness benefits of intergroup killing in one of our two closest living relatives and contribute to the debate regarding its adaptive significance.